Modified Taiji Stone and Its Application in Far-infrared Health-care Degradable Copolyester Fiber

By modifying Tai Chi stone powder, using polydiol and phthalate coupling agent containing alkyl side chains, it is dispersed well in the degradable copolyester, which solves the problems of poor dispersion and difficulty in degradation. It achieves efficient far infrared performance and good spinning ability.

CN116356440BActive Publication Date: 2025-02-07ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310163114.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-21
Publication Date
2025-02-07
Estimated Expiration
2043-02-21

AI Technical Summary

Technical Problem

In the prior art, Tai Chi stone powder has poor dispersion in polyester, resulting in high pressure on spinning equipment, and the polyester is not easy to degrade, which is harmful to the environment.

Method used

The Tai Chi stone powder is modified by polydiol and phthalate coupling agent containing alkyl side chains. After modification, Tai Chi stone is well dispersed in the degradable copolyester, and the spinning process has little pressure on the equipment. Improves the degradability of copolyesters.

Benefits of technology

Modified Tai Chi stone significantly improves far-infrared performance in copolyester fibers, improves blood flow and blood flow velocity, and has excellent health care effects. In addition, copolyester fibers are spinned well during spinning, and the component pressure rises slowly. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004094900580000111
    Figure BDA0004094900580000111
  • Figure BDA0004094900580000112
    Figure BDA0004094900580000112
  • Figure BDA0004094900580000121
    Figure BDA0004094900580000121
Patent Text Reader

Abstract

The present invention relates to the field of functional textile materials, and discloses a modified Taiji stone and its application in far-infrared health-care degradable copolyester fibers. The modified Taiji stone of the present invention comprises Taiji stone powder; polyglycol containing alkyl side chains adsorbed on the surface of the Taiji stone powder; and phthalate coupling agent coated on the surface of the polyglycol. The present invention successively adopts polyglycol containing alkyl side chains and phthalate coupling agent to modify Taiji stone powder, the method is simple and easy to operate, the modified Taiji stone is well dispersed in the degradable copolyester, the spinning process has less pressure on the equipment, and the degradability of the copolyester can be enhanced; the present invention adds the modified Taiji stone to the degradable copolyester fiber, which can significantly improve the far-infrared performance and has excellent health-care effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of functional textile materials, in particular to a modified Tai Chi stone and application thereof in far-infrared health-care degradable copolyester fibers. Background Art

[0002] Since DuPont started industrial production of polyester in 1953, polyester has been widely used for its excellent performance and low price, one of which is as pillow filling. Due to the rapid development of society, residents' consumption concepts are also quietly changing. People are not only satisfied with the practicality of pillows, but also pay more attention to their health benefits.

[0003] Taiji stone is a natural ore, which contains a variety of trace metal mineral elements, can radiate far infrared rays, promote blood microcirculation, metabolism, and has certain health care functions. The Chinese invention patent with publication number CN105420835A discloses a method for manufacturing antibacterial far-infrared health-care polyester fiber. The invention blends Taiji stone powder, antibacterial functional materials and polyester, and melt-extrudes them into antibacterial far-infrared masterbatch through screw; then the masterbatch is spun with polyester slices to form antibacterial far-infrared health-care polyester fiber. The fiber fabric has a far-infrared normal emissivity of >0.8, blood flow and blood flow velocity increase by >30%, and the health care effect is obvious. However, in the antibacterial far-infrared health-care polyester fiber prepared by this method, Taiji stone powder is directly added to the blend without modification, and it is easy to agglomerate in polyester, with poor dispersibility and high pressure on spinning equipment. On the other hand, polyester is difficult to degrade in the soil, and its waste has a great damage to the natural environment and ecosystem. The existing technology lacks the research, development and preparation of far-infrared biodegradable polyesters. Therefore, if a far-infrared biodegradable polyester with uniform dispersion of far-infrared inorganic materials, easy spinning and good biodegradability can be successfully developed, it can meet the market demand. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a modified Taiji stone and its application in far-infrared health-care degradable copolyester fiber. First, the present invention provides a modified Taiji stone and a preparation method thereof. The present invention successively uses polyglycol containing alkyl side chains and phthalate coupling agent to modify Taiji stone powder. The method is simple and easy to operate. The modified Taiji stone is well dispersed in the degradable copolyester. The spinning process has less pressure on the equipment and can enhance the degradability of the copolyester. Secondly, the present invention provides a far-infrared health-care degradable copolyester fiber containing modified Taiji stone and a preparation method thereof, which can significantly improve the far-infrared performance and have excellent health-care effects.

[0005] The specific technical scheme of the present invention is:

[0006] In the first aspect, the present invention provides a modified Tai Chi stone, comprising: Tai Chi stone powder; a polyglycol containing alkyl side chains adsorbed on the surface of the Tai Chi stone powder, the alkyl side chains of the polyglycol being entangled with each other; and a phthalate coupling agent coated on the surface of the polyglycol containing alkyl side chains.

[0007] The present invention successively adopts polyglycol containing alkyl side chains and phthalate coupling agent to modify Taiji stone powder. Taiji stone is mainly composed of silicon dioxide, and polyglycol has a strong adsorption effect on silicon molecules. Through its adsorption on the surface of Taiji stone particles, the agglomeration of Taiji stone particles can be prevented. In addition, the alkyl side chains of polyglycol will be entangled with each other to promote the agglomeration of Taiji stone particles, so that the particle size of the system tends to be uniform; in addition, the introduction of polyglycol improves the hydrophilicity of copolyester, which is conducive to the entry of water molecules, thereby improving the degradation performance of copolyester materials. The alkoxy group of the terminal group of phthalate coupling agent and the hydroxyl group of the terminal of polypropylene glycol are loaded on the surface of Taiji stone through electrophilic effect, and at the same time, the metal titanium ion in the phthalate coupling agent is coordinated and combined with the carbonyl oxygen on the polyester chain segment during the polymerization process. The modified Taiji stone is loaded on the copolyester chain segment and has good structural stability. The function of the dispersant is to reduce the interfacial tension between liquid-solid and liquid-liquid, which can improve the anti-agglomeration ability of Taiji stone powder and maintain the stability of the dispersion.

[0008] In summary, the modified Taiji stone of the present invention is well dispersed in the degradable copolyester, and the spinning process has less pressure on the equipment. When it is added to the copolyester fiber, the blood flow and blood flow velocity of the copolyester fiber are significantly improved after testing, and it has excellent health care effects.

[0009] Preferably, the polyglycol containing an alkyl side chain is polypropylene glycol having a molecular weight of 500 to 2000.

[0010] In order to further enhance the particle size uniformity of the Tai Chi Stone particles by the polyglycol, the present invention preferably uses polypropylene glycol with a molecular weight of 500 to 2000. The reason is that, on the one hand, the side methyl group length of the alkyl side chain of polypropylene glycol is relatively short, and on the basis of being able to be entangled to a certain extent, the viscosity of the polyglycol will not be too high due to the excessive length of the carbon chain. On the other hand, polypropylene glycol with a suitable molecular weight can avoid entanglement between polypropylene glycols due to the excessive length of the main chain, thereby showing a poor wrapping effect on the Tai Chi Stone. Preferably, the particle size of the Tai Chi Stone powder is 100 to 300 nm.

[0011] Preferably, the phthalate coupling agent is one or more of isopropoxy triphthalate, isopropyl dioleyl phthalate, and monoalkoxy unsaturated fatty acid phthalate.

[0012] In the second aspect, the present invention provides a method for preparing a modified Tai Chi stone, comprising: crushing, calcining and grinding Tai Chi stone ore to obtain Tai Chi stone powder, dispersing the Tai Chi stone powder in an organic solvent, adding a polyglycol containing an alkyl side chain under stirring conditions, introducing an inert gas, adjusting the pH to neutral or alkaline, heating to reflux reaction, then adding a phthalate coupling agent and a dispersant for constant temperature reaction, and filtering, washing and drying in sequence to obtain the modified Tai Chi stone.

[0013] Preferably, the calcination temperature is 800-1200° C. and the calcination time is 3-8 hours.

[0014] Preferably, the mass ratio of the polyglycol containing alkyl side chains to the Taichi stone powder is 0.01-0.2:1.

[0015] Preferably, the mass ratio of the phthalate coupling agent to the Taiji stone powder is 0.001-0.02:1.

[0016] Preferably, the dispersant is one or more of sodium tripolyphosphate, polyhydroxystearic acid, sodium hexametaphosphate and sodium lauryl sulfate.

[0017] Preferably, the mass ratio of the dispersant to the Tai Chi stone powder is 0.001-0.005:1.

[0018] Preferably, the organic solvent is toluene.

[0019] Preferably, the pH is adjusted to 7-9 after the inert gas is introduced.

[0020] Preferably, the reflux reaction time is 3 to 5 hours.

[0021] Preferably, the isothermal reaction time is 5 to 8 hours.

[0022] Preferably, the drying is vacuum drying at a temperature of 50 to 80° C. for 12 to 24 hours.

[0023] In a third aspect, the present invention provides the use of the modified Tai Chi stone in far-infrared health-care degradable copolyester fibers.

[0024] In a fourth aspect, the present invention provides a far-infrared health-care degradable copolyester fiber containing the modified Tai Chi stone, comprising the following raw materials:

[0025] a) aromatic dibasic acid and / or aromatic dibasic acid diol ester;

[0026] b) aliphatic dibasic acids and / or diol esters of aliphatic dibasic acids;

[0027] c) diols;

[0028] d) Modified Tai Chi Stone.

[0029] Among them, the modified Taiji stone is loaded on the copolyester chain segment by the metal titanium ion of the phthalate coupling agent being coordinated and modified with the carbonyl oxygen on the copolyester chain segment during the polymerization process.

[0030] The modified Taiji stone of the present invention is well dispersed in the degradable copolyester, and the spinning process has less pressure on the equipment. When it is added to the copolyester fiber, the blood flow and blood flow velocity of the copolyester fiber are significantly improved after testing, and it has excellent health care effect.

[0031] Preferably, the aromatic dibasic acid includes one or more of terephthalic acid, 1,4-naphthalene dicarboxylic acid, isophthalic acid and biphenyl dicarboxylic acid.

[0032] Preferably, the aromatic dibasic acid diol ester includes one or more of dimethyl terephthalate, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dimethyl 1,4-naphthalate, diethyl 1,4-naphthalate, dipropyl 1,4-naphthalate, dibutyl 1,4-naphthalate, dimethyl isophthalate, diethyl isophthalate, dipropyl isophthalate, dibutyl isophthalate, dimethyl biphenyl, diethyl biphenyl, dipropyl biphenyl and dibutyl biphenyl.

[0033] Preferably, the aliphatic dibasic acid comprises one or more of oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid.

[0034] Preferably, the aliphatic dibasic acid diol ester comprises one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate, dimethyl succinate, diethyl succinate, dipropyl succinate, dibutyl succinate, dimethyl glutarate, diethyl glutarate, dipropyl glutarate, dibutyl glutarate, dipropyl adipate, dibutyl adipate, dimethyl adipate, diethyl adipate, dimethyl pimelate, diethyl pimelate, dipropyl pimelate, dibutyl pimelate, dimethyl suberate, diethyl suberate, dipropyl suberate, dibutyl suberate, dimethyl azelate, diethyl azelate, dipropyl azelate, dibutyl azelate, dimethyl sebacate, diethyl sebacate, dipropyl sebacate and dibutyl sebacate.

[0035] Preferably, the diol includes one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol.

[0036] Preferably, the molar ratio of the total amount of the dibasic acid and the dibasic acid diol ester to the diol is 1:1.1-3.

[0037] Preferably, the molar ratio of the total amount of the aromatic dibasic acid and the aromatic dibasic acid diol ester to the total amount of the aliphatic dibasic acid and the aliphatic dibasic acid diol ester is 1:3 to 3:1;

[0038] Preferably, the added amount of the modified Taiji stone is 0.1-5% of the total mass of the dibasic acid and the dibasic acid diol ester.

[0039] In a fifth aspect, the present invention provides a method for preparing a far-infrared health-care degradable copolyester fiber, comprising the following steps:

[0040] 1) Esterification reaction: Aromatic dibasic acid and / or aromatic dibasic acid diol ester, aliphatic dibasic acid and / or aliphatic dibasic acid diol ester, diol, modified Taiji stone, catalyst and stabilizer are first subjected to normal pressure esterification reaction at 160-190°C, and then subjected to pressure esterification reaction at 220-240°C and 0.2-0.4MPa.

[0041] 2) Polycondensation reaction to obtain copolyester chips.

[0042] 3) Spinning.

[0043] In the above-mentioned preparation method of the present invention, the esterification reaction adopts a two-step esterification, wherein the normal pressure esterification is the esterification of the aliphatic dibasic acid, and the pressurized esterification is the esterification of the aromatic dibasic acid. The advantage is that since the heat resistance of the aliphatic dibasic acid is weaker than that of the aromatic dibasic acid, the aliphatic dibasic acid esterification process is more likely to have side reactions at high temperatures, and the two-step esterification can effectively improve the utilization rate of the aliphatic dibasic acid monomer.

[0044] Preferably, the catalyst is one or more of antimony glycolate, antimony trioxide, stannous octoate, stannous oxalate, stannous chloride, tetrabutyl titanate, tetrapropyl titanate, titanium acetate and titanium tetrachloride.

[0045] Preferably, the amount of the catalyst is 0.01 to 1% of the total mass of the dibasic acid and the dibasic acid diol ester;

[0046] Preferably, the stabilizer is one or more of triphenyl phosphate, phosphoric acid, alkyl phosphate and alkyl diaryl phosphate.

[0047] Preferably, the amount of the stabilizer is 0.05-0.5% of the total mass of the dibasic acid and the dibasic acid diol ester.

[0048] Compared with the prior art, the present invention has the following technical effects:

[0049] (1) The present invention successively uses a polyglycol containing an alkyl side chain and a phthalate coupling agent to modify the Taiji stone powder. The method is simple and easy to operate. The modified Taiji stone is well dispersed in the degradable copolyester. The spinning process puts less pressure on the equipment and can enhance the degradability of the copolyester.

[0050] (2) The present invention adds modified Tai Chi stone to the degradable copolyester fiber, which can significantly improve the far-infrared performance and has excellent health care effects.

[0051] (3) The present invention adopts a two-step esterification process in the esterification process of preparing the copolyester, wherein the esterification of the aliphatic dibasic acid is carried out at normal pressure, and the esterification of the aromatic dibasic acid is carried out at pressurized pressure. Since the heat resistance of the aliphatic dibasic acid is weaker than that of the aromatic dibasic acid, side reactions are more likely to occur during the esterification process of the aliphatic dibasic acid at high temperature. The two-step esterification can effectively improve the utilization rate of the aliphatic dibasic acid monomer.

[0052] (4) The raw materials of the present invention are cheap and readily available, the preparation process is simple, and it is convenient for industrial production. DETAILED DESCRIPTION

[0053] The present invention will be further described below in conjunction with the embodiments.

[0054] Overall embodiment

[0055] A modified Taiji stone comprises: Taiji stone powder; polyglycol containing alkyl side chains adsorbed on the surface of the Taiji stone powder; and a phthalate coupling agent coated on the surface of the polyglycol containing alkyl side chains; wherein the alkyl side chains of the polyglycol containing alkyl side chains are entangled with each other, and the polyglycol containing alkyl side chains is preferably polypropylene glycol with a molecular weight of 500 to 2000. The alkoxy group at the end group of the phthalate coupling agent is combined with the hydroxyl group at the end of the polyglycol through an electrophilic effect.

[0056] A preparation method of modified Taiji stone comprises: crushing Taiji stone ore, calcining (preferably at 800-1200°C, 3-8h), grinding to obtain Taiji stone powder with a particle size of 100-300nm, dispersing the Taiji stone powder in an organic solvent (preferably toluene), adding polyglycol containing alkyl side chains (preferably the carbon chain length of the alkyl side chains is preferably 2-3) under stirring conditions, introducing inert gas, adjusting the pH to neutral or alkaline (preferably 7-9), heating and reflux reaction (3-5h), then adding a phthalate coupling agent (preferably isopropoxy triphthalate, isopropyl dioleyl acyl phthalate, monoalkoxy unsaturated fatty acid phthalate) and a dispersant (preferably sodium tripolyphosphate, polyhydroxystearic acid, sodium hexametaphosphate and sodium dodecyl sulfate) to react at a constant temperature (5-8h), filtering, washing and drying (preferably vacuum drying, 50-80°C, 12-24h) in sequence to obtain the modified Taiji stone. Among them, the mass ratio of polyglycol to Taiji stone powder is 0.01-0.2:1; the mass ratio of phthalate coupling agent to Taiji stone powder is 0.001-0.02:1; the mass ratio of dispersant to Taiji stone powder is 0.001-0.005:1.

[0057] A far-infrared health-care biodegradable copolyester fiber containing modified Tai Chi stone, comprising the following raw materials:

[0058] a) aromatic dibasic acid and / or aromatic dibasic acid diol ester;

[0059] b) aliphatic dibasic acids and / or diol esters of aliphatic dibasic acids;

[0060] c) diols;

[0061] d) Modified Taiji Stone: The modified Taiji Stone is loaded on the copolyester chain segment by the metal titanium ion of the phthalate coupling agent being coordinated and combined with the carbonyl oxygen on the copolyester chain segment during the polymerization process.

[0062] Among them: the molar ratio of the total amount of dibasic acid and dibasic acid diol ester to diol is 1:1.1~3; the molar ratio of the total amount of aromatic dibasic acid and aromatic dibasic acid diol ester to the total amount of aliphatic dibasic acid and aliphatic dibasic acid diol ester is 1:3~3:1; the added amount of modified Tai Chi stone is 0.1~5% of the total mass of dibasic acid and dibasic acid diol ester.

[0063] The aromatic dibasic acid includes one or more of terephthalic acid, 1,4-naphthalene dicarboxylic acid, isophthalic acid and biphenyl diacid. The aromatic dibasic acid diol ester includes one or more of dimethyl terephthalate, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, 1,4-naphthalene dicarboxylic acid dimethyl ester, 1,4-naphthalene dicarboxylic acid diethyl ester, 1,4-naphthalene dicarboxylic acid dipropyl ester, 1,4-naphthalene dicarboxylic acid dibutyl ester, dimethyl isophthalate, diethyl isophthalate, dipropyl isophthalate, dibutyl isophthalate, dimethyl biphenyl diacid, diethyl biphenyl diacid, dipropyl biphenyl diacid and dibutyl biphenyl diacid. The aliphatic dibasic acid includes one or more of oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid. The aliphatic dibasic acid diol ester includes one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate, dimethyl succinate, diethyl succinate, dipropyl succinate, dibutyl succinate, dimethyl glutarate, diethyl glutarate, dipropyl glutarate, dibutyl glutarate, dipropyl adipate, dibutyl adipate, dimethyl adipate, diethyl adipate, dimethyl pimelate, diethyl pimelate, dipropyl pimelate, dibutyl pimelate, dimethyl suberate, diethyl suberate, dipropyl suberate, dibutyl suberate, dimethyl azelate, diethyl azelate, dipropyl azelate, dibutyl azelate, dimethyl sebacate, diethyl sebacate, dipropyl sebacate and dibutyl sebacate. The diol includes one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol.

[0064] A method for preparing far-infrared health-care degradable copolyester fiber comprises the following steps:

[0065] 1) Esterification reaction: Aromatic dibasic acid and / or aromatic dibasic acid diol ester, aliphatic dibasic acid and / or aliphatic dibasic acid diol ester, diol, modified Taiji stone, catalyst and stabilizer are added to the reaction kettle, the air in the kettle is first discharged with inert gas, the temperature is raised to 160-190°C for 0.5-3h normal pressure esterification reaction, and then pressure esterification is carried out at 220-240°C and 0.2-0.4MPa until the theoretical water output is more than 95%, and then enter the polycondensation reaction;

[0066] Preferably, the catalyst is one or more of antimony glycol, antimony trioxide, stannous octoate, stannous oxalate, stannous chloride, tetrabutyl titanate, tetrapropyl titanate, titanium acetate and titanium tetrachloride; the amount of the catalyst is 0.01-1% of the total mass of the dibasic acid and the dibasic acid diol ester; the stabilizer is one or more of triphenyl phosphate, phosphoric acid, alkyl phosphate and alkyl diaryl phosphate; the amount of the stabilizer is 0.05-0.5% of the total mass of the dibasic acid and the dibasic acid diol ester.

[0067] 2) Polycondensation reaction: After the esterification is completed, the temperature is raised to 240-260°C, and the vacuum is slowly drawn to remove the excess diol in the reaction. After 0.8-1.2 hours, the vacuum degree in the kettle reaches less than 60Pa. After 1.5-3 hours of polycondensation, the reaction is completed.

[0068] 3) Spinning: vacuum drying the copolyester chips at 80-120° C. for 12-24 hours, and spinning the chips through a circular spinneret after they are melted. The spinning process: the spinning temperature is 230-260° C., and the spinning winding speed is 2600-3200 m / min.

[0069] Example 1

[0070] (1) Preparation of modified Taichi stone:

[0071] The Taiji stone ore is crushed, calcined, and ground to obtain Taiji stone powder. The calcination temperature of Taiji stone is 1000℃, the calcination time is 5h, and the average particle size of the ground Taiji stone powder is 100-300nm. 50g Taiji stone powder with a particle size of 200nm is dispersed in 100g toluene, and 0.5g polypropylene glycol with a molecular weight of 1000 is added under mechanical stirring. Stirring is continued, nitrogen is introduced, and the pH is adjusted to 8. After heating and reflux reaction for 3h, 0.5g isopropoxy trititanate and 0.2g sodium tripolyphosphate are added to the reaction container. After the reaction is kept at a constant temperature of 90℃ for 5h, it is filtered and washed in turn, and vacuum dried at 70℃ for 12h to obtain modified Taiji stone;

[0072] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0073] 996.786g of terephthalic acid, 354.267g of succinic acid, 782.082g of ethylene glycol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into the kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletize it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0074] Example 2

[0075] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0076] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0077] 996.786g of terephthalic acid, 438.42g of adipic acid, 893.808g of ethylene glycol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into the kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletize it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0078] Example 3

[0079] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0080] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0081] 996.786g of terephthalic acid, 270.12g of oxalic acid, 782.082g of ethylene glycol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into the kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletized it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0082] Example 4

[0083] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0084] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0085] 747.590g of terephthalic acid, 531.405g of succinic acid, 782.082g of ethylene glycol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into the kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletize it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0086] Example 5

[0087] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0088] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0089] 996.786g of terephthalic acid, 354.267g of succinic acid, 1459.944g of 1,4-butanediol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletize it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0090] Example 6

[0091] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0092] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0093] 498.393g of terephthalic acid, 582.552g of dimethyl terephthalate, 354.267g of succinic acid, 1459.944g of 1,4-butanediol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletize it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a spinning device of LHV903 model. The spinning temperature was 240°C and the spinning winding speed was 2600m / min.

[0094] Example 7

[0095] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0096] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0097] 498.393g of terephthalic acid, 582.552g of dimethyl terephthalate, 177.135g of succinic acid, 219.21g of adipic acid, 1459.944g of 1,4-butanediol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into the kettle. After nitrogen was used to expel the air in the kettle, the temperature was raised to 180℃ and esterified at normal pressure for 0.5h. Then the temperature was raised to 180℃ and esterified at normal pressure for 0.5h. The temperature was raised to 230°C, and esterification was performed at 0.35MPa until the theoretical water output was more than 95%, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C, and the copolyester was obtained after reacting for 1.5 hours under a vacuum of 60Pa, and then the copolyester was pelletized. The copolyester chips were vacuum dried at 100°C for 18 hours, and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0098] Example 8

[0099] (1) The preparation of modified Tai Chi stone is the same as that in Example 1;

[0100] (2) Preparation of far-infrared health-care degradable copolyester fiber:

[0101] 996.786g of terephthalic acid, 354.267g of adipic acid, 391.041g of ethylene glycol, 729.972g of 1,4-butanediol, 5g of modified Taiji stone, 0.6g of ethylene glycol antimony and 0.3g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5h. The temperature was then raised to 230°C and esterified at 0.35MPa to more than 95% of the theoretical water output, and the esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60Pa for 1.5h to obtain copolyester and pelletize it. The copolyester slices were vacuum dried at 100°C for 18h and spun on a LHV903 spinning device at a spinning temperature of 240°C and a spinning winding speed of 2600m / min.

[0102] Comparative Example 1

[0103] (1) The difference from Example 1 is that no modified Tai Chi stone is added.

[0104] (2) 996.786 g of terephthalic acid, 354.267 g of succinic acid, 782.082 g of ethylene glycol, 0.6 g of ethylene glycol antimony and 0.3 g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180° C. and esterified at normal pressure for 0.5 h. The temperature was then raised to 230° C. and esterified at 0.35 MPa until the theoretical water output was more than 95%. The esterification was completed. In the polycondensation stage, the temperature was heated to 250° C. and reacted under a vacuum of 60 Pa for 1.5 h to obtain a copolyester, which was then pelletized. The copolyester chips were vacuum dried at 100° C. for 18 h and spun on a spinning device of model LHV903. The spinning temperature was 240° C. and the spinning winding speed was 2600 m / min.

[0105] Comparative Example 2

[0106] The difference from Example 1 is that unmodified Tai Chi stone powder is added.

[0107] (1) The Taiji stone ore is crushed, calcined, and ground to obtain Taiji stone powder. The calcination temperature of the Taiji stone is 1000° C., the calcination time is 5 h, and the average particle size of the ground Taiji stone powder is 100 to 300 nm.

[0108] (2) 996.786 g of terephthalic acid, 354.267 g of succinic acid, 782.082 g of ethylene glycol, 5 g of Taiji stone powder with a particle size of 200 nm, 0.6 g of ethylene glycol antimony and 0.3 g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5 h. The temperature was then raised to 230°C and esterified at 0.35 MPa to more than 95% of the theoretical water output. The esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60 Pa for 1.5 h to obtain copolyester and cut it into pellets. The copolyester chips were vacuum dried at 100°C for 18 h and spun on a spinning device of LHV903 at a spinning temperature of 240°C and a spinning winding speed of 2600 m / min.

[0109] Comparative Example 3

[0110] The difference from Example 1 is that the added modified Tai Chi stone is not treated with polypropylene glycol surface adsorption.

[0111] (1) Crush, calcine and grind the Taiji stone ore to obtain Taiji stone powder. The calcination temperature of Taiji stone is 1000°C, the calcination time is 5 hours, and the average particle size of the ground Taiji stone powder is 100-300 nm. Disperse 50 g of Taiji stone powder with a particle size of 200 nm in 100 g of toluene, add 0.5 g of isopropoxy trititanate and 0.2 g of sodium tripolyphosphate to the reaction container under mechanical stirring, react at a constant temperature of 90°C for 5 hours, filter and wash in turn, and vacuum dry at 70°C for 12 hours to obtain modified Taiji stone;

[0112] (2) 996.786 g of terephthalic acid, 354.267 g of succinic acid, 782.082 g of ethylene glycol, 5 g of modified Taiji stone, 0.6 g of ethylene glycol antimony and 0.3 g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5 h. The temperature was then raised to 230°C and esterified at 0.35 MPa until the theoretical water output was more than 95%. The esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60 Pa for 1.5 h to obtain a copolyester and cut it into pellets. The copolyester chips were vacuum dried at 100°C for 18 h and spun on a spinning device of LHV903 at a spinning temperature of 240°C and a spinning winding speed of 2600 m / min.

[0113] Comparative Example 4

[0114] The difference from Example 1 is that the added modified Taiji stone is not loaded with a phthalate coupling agent.

[0115] (1) Crush, calcine and grind the Taiji stone ore to obtain Taiji stone powder. The calcination temperature of Taiji stone is 1000°C and the calcination time is 5 hours. The average particle size of the ground Taiji stone powder is 100-300 nm. Disperse 50 g of Taiji stone powder with a particle size of 200 nm in 100 g of toluene, add 0.5 g of polypropylene glycol under mechanical stirring, continue stirring, introduce nitrogen, adjust the pH to 8, heat and reflux for 3 hours, filter and wash in turn, and vacuum dry at 70°C for 12 hours to obtain modified Taiji stone;

[0116] (2) 996.786 g of terephthalic acid, 354.267 g of succinic acid, 782.082 g of ethylene glycol, 5 g of modified Taiji stone, 0.6 g of ethylene glycol antimony and 0.3 g of triphenyl phosphate were mixed and added into a kettle. After the air in the kettle was discharged by nitrogen, the temperature was raised to 180°C and esterified at normal pressure for 0.5 h. The temperature was then raised to 230°C and esterified at 0.35 MPa until the theoretical water output was more than 95%. The esterification was completed. In the polycondensation stage, the temperature was heated to 250°C and reacted under a vacuum of 60 Pa for 1.5 h to obtain a copolyester and cut it into pellets. The copolyester chips were vacuum dried at 100°C for 18 h and spun on a spinning device of LHV903 at a spinning temperature of 240°C and a spinning winding speed of 2600 m / min.

[0117] Comparative Example 5

[0118] The difference from Example 1 is that the molecular weight of the polypropylene glycol is 8000.

[0119] (1) Preparation of modified Taichi stone:

[0120] The Taiji stone ore is crushed, calcined, and ground to obtain Taiji stone powder. The calcination temperature of Taiji stone is 1000℃, the calcination time is 5h, and the average particle size of the ground Taiji stone powder is 100-300nm. 50g Taiji stone powder with a particle size of 200nm is dispersed in 100g toluene, and 0.5g polypropylene glycol with a molecular weight of 8000 is added under mechanical stirring. Stirring is continued, nitrogen is introduced, and the pH is adjusted to 8. After heating and reflux reaction for 3h, 0.5g isopropoxy trititanate and 0.2g sodium tripolyphosphate are added to the reaction container. After the reaction is kept at a constant temperature of 90℃ for 5h, it is filtered and washed in turn, and vacuum dried at 70℃ for 12h to obtain modified Taiji stone;

[0121] (2) The preparation of far-infrared health-care degradable copolyester fiber is the same as in Example 1.

[0122] Performance Testing

[0123] (1) Far infrared test: obtained according to the standard FZ / T64010-2000;

[0124] (2) Blood flow and blood flow velocity: obtained according to the CAS115-2005 test standard;

[0125] (3) Degradation rate: 60-day degradation rate in soil burial degradation experiment; Soil burial degradation experiment: first, set up 3 groups of parallel experiments for each fiber in each embodiment and comparative example, randomly select 8 sample fibers from each group, and bury them in soil at a depth of 30 cm after weighing. The soil is watered every 10 days. The samples are taken out every 60 days, the surface soil is brushed off, and the samples are washed and vacuum dried at 40°C for 12 h. The changes in the mass of the samples before and after are recorded.

[0126] Table 1: Properties of copolyester fibers in various examples

[0127]

[0128] Table 2: Properties of copolyester fibers in various comparative examples

[0129]

[0130]

[0131] Table 3: Comparison of spinnability of various embodiments and comparative examples

[0132] Group Spinnability Example 1 Good spinnability, slow component pressure rise Example 2 Good spinnability, slow component pressure rise Example 3 Good spinnability, slow component pressure rise Example 4 Good spinnability, slow component pressure rise Example 5 Good spinnability, slow component pressure rise Example 6 Good spinnability, slow component pressure rise Example 7 Good spinnability, slow component pressure rise Example 8 Good spinnability, slow component pressure rise Comparative Example 1 Good spinnability, slow component pressure rise Comparative Example 2 Poor spinnability, difficult to raise the head, and the pressure of the component rises quickly Comparative Example 3 Spinnability preference, occasional ends down, slow rise in component pressure Comparative Example 4 Spinnability preference, occasional ends down, slow rise in component pressure Comparative Example 5 Spinnability preference, occasional ends down, slow rise in component pressure

[0133] Note: Spinning assembly pressure rise rate: Comparative Example 2>Comparative Example 3>Comparative Example 4>Comparative Example 5>Example 1

[0134] From the data comparison in Tables 1-3, we can see that:

[0135] The far-infrared health-care degradable copolyester fibers prepared in various embodiments of the present invention have significantly improved blood flow and blood flow velocity in the test, promoted human blood microcirculation, and had significant health-care effects; the copolyester chips prepared by adding the modified Tai Chi stone to the polymerization reaction have good spinnability during the spinning process, and the pressure of the components rises slowly; and the preparation method is simple and easy to operate, which is conducive to industrial production. Specifically:

[0136] Combining Example 1 with Comparative Example 1, the far-infrared effect of the copolyester fiber obtained after adding modified Tai Chi stone is significantly improved. Although the far-infrared performance of the copolyester fiber obtained by adding unmodified Tai Chi stone in Comparative Example 2 is also improved, its compatibility and dispersibility in the copolyester are poor, and it is easy to agglomerate, resulting in poor spinnability during the spinning process, difficulty in spinning, and a rapid increase in the pressure of the spinning assembly.

[0137] In combination with Example 1, Comparative Example 3 and Comparative Example 4, the agglomeration effect of the Taiji stone powder modified by the synergistic modification of polypropylene glycol and phthalate coupling agent in the copolyester is better than that of the single modification, the spinning condition is good, and the pressure rise of the assembly is slow.

[0138] In combination with Example 1 and Comparative Example 5, the molecular weight of polypropylene glycol is too large, and it is easy to get entangled with itself, resulting in a poor coating effect on the Tai Chi Stone.

[0139] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0140] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. The application of modified Taiji stone in far-infrared health-care degradable copolyester fiber is characterized by: The modified Taiji stone is loaded on the copolyester chain segment by the coordination and modification of the titanium ions of the phthalate coupling agent with the carbonyl oxygen on the copolyester chain segment during the polymerization process; the preparation of the modified Taiji stone includes: crushing, calcining and grinding the Taiji stone ore, dispersing the obtained Taiji stone powder in an organic solvent, adding polypropylene glycol with a molecular weight of 500-2000 under stirring, passing an inert gas, adjusting the pH to neutral or alkaline, heating to reflux reaction, adding a phthalate coupling agent and a dispersant for constant temperature reaction, filtering, washing and drying to obtain the modified Taiji stone; the modified Taiji stone includes: Taiji stone powder, polypropylene glycol adsorbed on the surface of the Taiji stone powder, and phthalate coupling agent coated on the surface of the polypropylene glycol; the alkyl side chains of the polypropylene glycol are entangled with each other; the alkoxy group at the end group of the phthalate coupling agent is combined with the hydroxyl group at the end of the polypropylene glycol through an electrophilic effect.

2. The use according to claim 1, characterized in that: The particle size of the Tai Chi stone powder is 100-300 nm.

3. The use according to claim 1, characterized in that: The phthalate coupling agent is one or more of isopropoxy triphthalate, isopropyl dioleyl phthalate, and monoalkoxy unsaturated fatty acid phthalate.

4. The use according to claim 1, characterized in that: The calcination temperature is 800-1200° C. and the calcination time is 3-8 hours.

5. The use according to claim 1, characterized in that: The mass ratio of the polypropylene glycol to the Taiji stone powder is 0.01-0.2:

1.

6. The use according to claim 1, characterized in that: The mass ratio of the phthalate coupling agent to the Taiji stone powder is 0.001-0.02:

1.

7. The use according to claim 1, characterized in that: The dispersant is one or more of sodium tripolyphosphate, polyhydroxystearic acid, sodium hexametaphosphate and sodium lauryl sulfate.

8. The use according to claim 1, characterized in that: The mass ratio of the dispersant to the Tai Chi stone powder is 0.001-0.005:

1.

9. The use according to claim 1, characterized in that: The organic solvent is toluene; After passing inert gas, adjust the pH to 7-9; The reflux reaction time is 3 to 5 hours; The isothermal reaction time is 5 to 8 hours; The drying is vacuum drying at a temperature of 50-80° C. for 12-24 hours.

10. A far-infrared health-care degradable copolyester fiber, characterized in that: Including the following ingredients: a) aromatic dibasic acid and / or aromatic dibasic acid diol ester; b) aliphatic dibasic acids and / or diol esters of aliphatic dibasic acids; c) diols; d) The modified Taichi stone in the application according to any one of claims 1 to 9; The modified Taiji stone is loaded on the copolyester chain segment through the coordination and combination modification of the metal titanium ions of the phthalate coupling agent with the carbonyl oxygen on the copolyester chain segment during the polymerization process.

11. The far-infrared health-care degradable copolyester fiber according to claim 10, characterized in that: The aromatic dibasic acid includes one or more of terephthalic acid, 1,4-naphthalene dicarboxylic acid, isophthalic acid and biphenyl dicarboxylic acid; The aromatic dibasic acid diol ester includes one or more of dimethyl terephthalate, diethyl terephthalate, dipropyl terephthalate, dibutyl terephthalate, dimethyl 1,4-naphthalate, diethyl 1,4-naphthalate, dipropyl 1,4-naphthalate, dibutyl 1,4-naphthalate, dimethyl isophthalate, diethyl isophthalate, dipropyl isophthalate, dibutyl isophthalate, dimethyl biphenyl, diethyl biphenyl, dipropyl biphenyl and dibutyl biphenyl; The aliphatic dibasic acid includes one or more of oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and sebacic acid; The aliphatic dibasic acid diol ester comprises one or more of dimethyl oxalate, diethyl oxalate, dipropyl oxalate, dibutyl oxalate, dimethyl succinate, diethyl succinate, dipropyl succinate, dibutyl succinate, dimethyl glutarate, diethyl glutarate, dipropyl glutarate, dibutyl glutarate, dipropyl adipate, dibutyl adipate, dimethyl adipate, diethyl adipate, dimethyl pimelate, diethyl pimelate, dipropyl pimelate, dibutyl pimelate, dimethyl suberate, diethyl suberate, dipropyl suberate, dibutyl suberate, dimethyl azelate, diethyl azelate, dipropyl azelate, dibutyl azelate, dimethyl sebacate, diethyl sebacate, dipropyl sebacate and dibutyl sebacate; The diol includes one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol and 1,10-decanediol.

12. The far-infrared health-care degradable copolyester fiber according to claim 10, characterized in that: The molar ratio of the total amount of the dibasic acid and the dibasic acid diol ester to the diol is 1:1.1-3; The molar ratio of the total amount of the aromatic dibasic acid and the aromatic dibasic acid diol ester to the total amount of the aliphatic dibasic acid and the aliphatic dibasic acid diol ester is 1:3 to 3:1; The added amount of the modified Taiji stone is 0.1-5% of the total mass of the dibasic acid and the dibasic acid diol ester.

13. A method for preparing the far-infrared health-care degradable copolyester fiber as claimed in any one of claims 10 to 12, characterized in that The following steps are involved: 1) Esterification reaction: Aromatic dibasic acid and / or aromatic dibasic acid diol ester, aliphatic dibasic acid and / or aliphatic dibasic acid diol ester, diol, modified Taiji stone, catalyst and stabilizer are first subjected to normal pressure esterification reaction at 160-190°C, and then subjected to pressure esterification reaction at 220-240°C and 0.2-0.4MPa; 2) Polycondensation reaction to obtain copolyester chips; 3) Spinning.

14. The preparation method according to claim 13, characterized in that: The catalyst is one or more of antimony glycol, antimony trioxide, stannous octoate, stannous oxalate, stannous chloride, tetrabutyl titanate, tetrapropyl titanate, titanium acetate and titanium tetrachloride; The amount of the catalyst is 0.01-1% of the total mass of the dibasic acid and the dibasic acid diol ester; The stabilizer is one or more of triphenyl phosphate, phosphoric acid, alkyl phosphate and alkyl diaryl phosphate; The amount of the stabilizer is 0.05-0.5% of the total mass of the dibasic acid and the dibasic acid diol ester.

Citation Information

Patent Citations

  • Manufacturing method of antibacterial and far infrared health polyester fibers

    CN105420835A

  • Preparation method of nano magnesium hydroxide modified degradable copolyester

    CN114573956A

  • Hydrophobic inorganic oxide fine powder, production method therefor and its use

    JP2003176107A